2012
DOI: 10.1074/jbc.m112.377945
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Activator of Nuclear Factor κB Ligand (RANKL) Protein Expression by B Lymphocytes Contributes to Ovariectomy-induced Bone Loss

Abstract: Background:The contribution of B lymphocytes to the bone loss caused by estrogen deficiency is unclear. Results: Deletion of the cytokine receptor activator of NFB ligand from B lymphocytes, but not T lymphocytes, blunted bone loss in ovariectomized mice. Conclusion: Cytokine production by B lymphocytes contributes to ovariectomy-induced bone loss. Significance: This mechanism may be relevant to the mechanisms responsible for postmenopausal osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
179
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 213 publications
(202 citation statements)
references
References 53 publications
12
179
1
4
Order By: Relevance
“…Consistent with this finding, deletion of ER␣ from osteocytes has no effect on osteoclast number (26,27). We and others have shown that the amount of soluble RANKL protein in bone marrow supernatants does increase with either estrogen or androgen deficiency (12,28,29). However, whether this increase in soluble RANKL contributes to the increase in bone resorption caused by these conditions is unknown.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Consistent with this finding, deletion of ER␣ from osteocytes has no effect on osteoclast number (26,27). We and others have shown that the amount of soluble RANKL protein in bone marrow supernatants does increase with either estrogen or androgen deficiency (12,28,29). However, whether this increase in soluble RANKL contributes to the increase in bone resorption caused by these conditions is unknown.…”
Section: Discussionsupporting
confidence: 68%
“…The latter finding was unexpected given that RANKL produced by B lymphocytes themselves is also required for this phenomenon (12). The mechanisms by which osteocyte RANKL controls B cell number are unclear but appear to be indirect as deletion of the receptor for RANKL from B cells does not alter B cell number (19).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…48 The number of RANKL-expressing B lymphocytes in the bone marrow increases after OVX. 49 Recently, Onal et al 50 demonstrated that RANKL produced by B cells and not by T cells have a role in OVX-induced bone loss in mice. This paper disagrees with previous reports showing a fundamental role of RANKL produced by T cells in OVX-induced bone loss.…”
Section: Inflammatory Diseases Immune System and Bonementioning
confidence: 99%